Case report: Nocardia farcinica pneumonia in early-stage post liver transplantation - Pan, Bing; Wang, Fang-Fei; He, Qiang (Frontiers in Medicine, 2022)
Background Liver transplantation is a well-established treatment for end-stage liver disease. The evolution of immunosuppressants has supported the recent advances in this field. However, this leads to immunosuppression and increases the risk for infections. Nocardia is an aerobic gram-positive bacillus, which can cause multi-systemic or multi-organ infections. Nocardia is an opportunistic pathogen that principally affects immunosuppressed patients. Case presentation Herein, we present a case of Nocardia farcinica pneumonia in a patient at early-stage post-liver transplantation. Following appropriate microbiological tests and imaging, the diagnosis was finally confirmed. A full recovery was achieved after optimal antibiotic therapy of sulfamethoxazole, minocycline, and amikacin. Conclusions Nocardia farcinica pneumonia is a rare and life-threatening disease, especially in patients after liver transplantation. Imaging and microbiological tests are helpful for the early diagnosis of the disease. Trimethoprim-sulfamethoxazole (TMP-SMX) as part of first-line therapy for nocardiosis is recommended.